2001
DOI: 10.1099/0022-1317-82-5-1013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the aphthovirus 2A/2B polyprotein ‘cleavage’ mechanism indicates not a proteolytic reaction, but a novel translational effect: a putative ribosomal ‘skip’

Abstract: The 2A region of the aphthovirus foot-and-mouth disease virus (FMDV) polyprotein is only 18 aa long. A ' primary ' intramolecular polyprotein processing event mediated by 2A occurs at its own C terminus. FMDV 2A activity was studied in artificial polyproteins in which sequences encoding reporter proteins flanked the 2A sequence such that a single, long, open reading frame was created. The self-processing properties of these artificial polyproteins were investigated and the co-translational ' cleavage ' product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
611
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 698 publications
(631 citation statements)
references
References 41 publications
17
611
0
3
Order By: Relevance
“…Insertion of the aphthovirus 2A oligopeptide into a polyprotein was sufficient to detect the individual polypeptides, although the upstream 2A product was in molar excess relative to the downstream product http://dx.doi.org/10.1016/j.virusres.2015.01.012 0168-1702/© 2015 Elsevier B.V. All rights reserved. (Donnelly et al, 2001). These results lead to the proposal that 2A was a translational recoding element (CHYSEL for cis-acting hydrolytic element, also referred to as stop/go translation).…”
Section: Picornavirus Genome Organizationmentioning
confidence: 96%
“…Insertion of the aphthovirus 2A oligopeptide into a polyprotein was sufficient to detect the individual polypeptides, although the upstream 2A product was in molar excess relative to the downstream product http://dx.doi.org/10.1016/j.virusres.2015.01.012 0168-1702/© 2015 Elsevier B.V. All rights reserved. (Donnelly et al, 2001). These results lead to the proposal that 2A was a translational recoding element (CHYSEL for cis-acting hydrolytic element, also referred to as stop/go translation).…”
Section: Picornavirus Genome Organizationmentioning
confidence: 96%
“…Processing of the IntF2A‐based polyprotein is initiated during protein translation, in which peptide bond formation between the last two amino acids of the F2A peptide, that is glycine and proline, is disrupted by the unique translational recoding activity of the F2A sequence (Donnelly et al ., 2001b). It has been hypothesized that the translational recoding event requires specific interaction of the ribosome exit tunnel with the nascent 2A peptide to constrain the conformational space of the peptidyl(2A)‐tRNA gly ester bond in the ribosome P‐site to ‘jam’ further elongation (Minskaia et al ., 2013; Roulston et al ., 2016; Yan et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Polyprotein expression based on the unique ribosome skipping mechanism of the FMDV 2A (F2A) peptide (Donnelly et al ., 2001b) operates cotranslationally. The F2A peptide has been used to direct multiprotein co‐expression in a wide range of eukaryotic hosts (de Felipe, 2004; de Felipe et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, the recent studies showed that there is a ribosome skipping between 2A and 2B junction, which results in the production of P1 polyprotein of 80 kDa [11,33]. Along with 28 aa of L-protease the size of the fusion protein is 83 kDa which was the observed molecular weight.…”
Section: Discussionmentioning
confidence: 99%